2018
DOI: 10.1073/pnas.1720298115
|View full text |Cite
|
Sign up to set email alerts
|

Heme redox potentials hold the key to reactivity differences between nitric oxide reductase and heme-copper oxidase

Abstract: Despite high structural homology between NO reductases (NORs) and heme-copper oxidases (HCOs), factors governing their reaction specificity remain to be understood. Using a myoglobin-based model of NOR (FeMb) and tuning its heme redox potentials (E°') to cover the native NOR range, through manipulating hydrogen bonding to the proximal histidine ligand and replacing heme with monoformyl (MF-) or diformyl (DF-) hemes, we herein demonstrate that the E°' holds the key to reactivity differences between NOR and HCO.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 44 publications
1
48
0
Order By: Relevance
“…In this study, the results of various vibrational, spectroscopic, electrochemical, and computational methods performed on the different heme-containing model systems showed that these rate determining factors for NO reduction can be controlled by tuning heme E°ˊ to achieve ~35 turnovers (based on quantification of N 2 O production using GC/MS), which is more than any previous synthetic (small molecule) or engineered protein system. 1115 This result was obtained with the Fe B Mb(MF-heme) protein which contains a monoformylated (Figure 143) heme with E°' = +53 ± 7 mV versus SHE. The significance of these results is further relevant for understanding the even wider variation in functions observed with other heme proteins as well (O 2 -transporting globins, vs O 2 -activating HCOs and P450s, vs NORs), which all have evolutionarily tuned heme environments and redox potentials.…”
Section: Small Molecule Synthetic Models Of Heme-copper Oxidasesmentioning
confidence: 83%
See 1 more Smart Citation
“…In this study, the results of various vibrational, spectroscopic, electrochemical, and computational methods performed on the different heme-containing model systems showed that these rate determining factors for NO reduction can be controlled by tuning heme E°ˊ to achieve ~35 turnovers (based on quantification of N 2 O production using GC/MS), which is more than any previous synthetic (small molecule) or engineered protein system. 1115 This result was obtained with the Fe B Mb(MF-heme) protein which contains a monoformylated (Figure 143) heme with E°' = +53 ± 7 mV versus SHE. The significance of these results is further relevant for understanding the even wider variation in functions observed with other heme proteins as well (O 2 -transporting globins, vs O 2 -activating HCOs and P450s, vs NORs), which all have evolutionarily tuned heme environments and redox potentials.…”
Section: Small Molecule Synthetic Models Of Heme-copper Oxidasesmentioning
confidence: 83%
“…In the modified Mb models, by changing the identity of the incorporated heme or the H-bonding to the proximal His ligand (which effectively lowers the heme redox potential), 309 they were able to tune the heme iron E°' and, in doing so, observed a significant enhancenment in NOR activity at lower heme potentials. 1115 The key to NO reduction in NORs is balancing the energetic favorability of (i) NO binding, (ii) Fe-NO decay, and (iii) electron transfer to the (heme)Fe-NO intermediate, analogous to the necessity for HCOs to control O 2 binding, ROS release, and PCET to the bound oxy ligand. All of these processes are affected by heme redox potentials.…”
Section: Small Molecule Synthetic Models Of Heme-copper Oxidasesmentioning
confidence: 99%
“…Rational design of the Mb distal site has been adopted to install HCOlike [123,124] and NOR-like [125] active sites, adding a new mononuclear cofactor. These putative Cu B and Fe B sites, together with heme, were not only structural and functional mimetics but were helpful in elucidating key aspects about the activity of their natural counterparts [126][127][128]. More recently, cytochrome c peroxidase (CcP) activity was steered toward an active SiR surrogate by installing a [4Fe-4S] cofactor in its proximal site [129].…”
Section: Engineering Natural Scaffoldsmentioning
confidence: 99%
“…2). 11,124 In Fig. 25 (left part) the energy profile for mechanism I in cbb 3 oxidases is compared to the corresponding profile for the a 3 oxidases, starting from the nitrosyl complex.…”
Section: No Reduction In Ccosmentioning
confidence: 99%